SOBRESSEMEADURA EM TIFTON 85 SUBMETIDO À FENAÇÃO: ESTABELECIMENTO DE FORAGEIRAS DE INVERNO - Zorzella, Marinei D.; Maixner, Adriano R.; Londero, Ana L.; Dreilich, Nailene D.; Krahn, Jaqueline R. T.; Uhde, Leonir T. (Salão do Conhecimento, 2013)
Resumo